Human papillomavirus (HPV) in women screenedto cervical uterine cancer, Belém – Pará – Brazil - Noronha, Vânia Lúcia; Cruz, Ermelinda M; Pinho, Cecília N; Mello, Wyller A; Villa, Luisa L; Russomano, Fábio B (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: human papillomavirus (HPV) is the agent of cervical uterine cancer. Objective: determine the prevalence of genital infection due to HPV and their correlation with results in the oncotic cytology. Methods: in a cross-sectional study, 1021 women, age 30 to 45 years were enrolled and submitted to cervical cancer screening. All patients answered a standard protocol. Samples of the uterine cervix were sent to citopathological analysis and to identification of HPV. Results: prevalence of HPV was 12.4%; in women with normal cervical cytology the prevalence of HPV was 8,7% compared to 43,4% in women with altered cervical cytology (28.9% among women with ASCUS/AGUS; 60.0% among women with LSIL; 90.0% among women with HSIL and 100.0% both in women with invasive carcinoma and in situ adenocarcinoma). Chance of detection of HSIL was 94 times higher in women who had HPV in the uterine cervix. A separate analysis including only the 116 HPV infected women revealed that HPV oncogenic types corresponded to 79.3% of the cases (71.8% in women with negative cervical cytology and 91.1% in women with altered cervical cytology). The frequency of oncogenic HPV types in 116 women infected with HPV was 79.3% [71.8% in women with negative citology and 91.1% in women with abnormalities in the citology exam). The odds to detect abnormalities in the citopatology exam was four times greater in the presence of HPV of high risk. HPV 16 was the most frequent type observed (24.4% of women with abnormal cytology and in 7,0% of those with negative cytology). Multiinfection was detected in 5.7% of women with abnormal cytology and in 1.1% with negative cytology. Conclusion: in this study, HPV infection and abnormal cytological findings in the uterine cervix were frequently observed and there was an association between them.